2021
DOI: 10.1007/s00203-021-02527-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of mutations in the SARS-CoV-2 RNA-dependent RNA polymerase as a promising antiviral therapeutic target

Abstract: The causative agent of COVID-19 is a novel betacoronavirus or severe acute respiratory syndrome coronavirus (SARS-CoV-2), which has emerged as a pandemic of global concern. Considering its rapid transmission, WHO has declared public health emergency on 11th March 2020 worldwide. SARS-CoV-2 is a genetically diverse positive sense RNA virus that typically exhibit high rates of mutation than DNA viruses. Higher rates of mutation bring higher genomic variability which may lead to viral evolution and enabling virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…In this study, we evaluated several mutations of the RdRp enzyme extracted from Saudi Arabia SARS-CoV-2 isolates and aligned them with the Wuhan RdRp enzyme to highlight key mutations that effect the enzyme structure, function and dynamics and overall virus pathogenicity, transmissibility and disease mortality. The findings of this study were found to be consistent with those of Pachetti et al [ 5 ] and Yashvardhini et al [ 27 ], who described the RdRp of SARS-CoV-2 acquiring drug-resistance properties due to the occurrence of a high frequency of mutations in the RdRp of infected populations worldwide and in India, respectively. The findings will not only give key findings to the society of the virus pathogenic strains circulating in Saudi Arabia but also will guide the discovery of novel drugs.…”
Section: Introductionsupporting
confidence: 92%
“…In this study, we evaluated several mutations of the RdRp enzyme extracted from Saudi Arabia SARS-CoV-2 isolates and aligned them with the Wuhan RdRp enzyme to highlight key mutations that effect the enzyme structure, function and dynamics and overall virus pathogenicity, transmissibility and disease mortality. The findings of this study were found to be consistent with those of Pachetti et al [ 5 ] and Yashvardhini et al [ 27 ], who described the RdRp of SARS-CoV-2 acquiring drug-resistance properties due to the occurrence of a high frequency of mutations in the RdRp of infected populations worldwide and in India, respectively. The findings will not only give key findings to the society of the virus pathogenic strains circulating in Saudi Arabia but also will guide the discovery of novel drugs.…”
Section: Introductionsupporting
confidence: 92%
“…According to Yashvardhini et al , the mutation in which tyrosine is replaced by cysteine (Indian variant) increased the structural flexibility of the enzyme and hence can influence the viral replication. 70 Note that the docking results for this mutant are shown in Table 5 . By observing these results, we can notice that the compounds have a nice affinity in the mutant RdRp active site, with energy values ranging from of −5.4 to −5.6 kcal mol −1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, ledipasvir, another nucleoside analog, has been approved for the treatment of SARS-CoV2 infection. Furthermore, certain mutations in RdRp are reported to cause resistance to remdesivir (5). Therefore, focused research studies are required to characterize mutations to understand the effect on drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Newer drugs, including ledipasvir, have been sanctioned for the treatment of SARS-CoV2 infection (4). The continuous emergence of variants throughout the globe highlights the importance to characterize replication related mutations in order to understand drug resistance (5). Furthermore, the correlation of mutations with diseases severity needs to be assessed.…”
Section: Introductionmentioning
confidence: 99%